Antenatal urolithiasis: A case report - Bose, Sumona; Iyengar, Arpana; Shubha, Attibele Mahadevaiah (Frontiers in Pediatrics, 2022)
Abstract Introduction - Pediatric urolithiasis, though an established entity, its antenatal diagnosis is rare. We hereby report a case detected at 20 weeks gestation and discuss the etiopathogenesis, predisposition and surveillance following intervention Case report - A 2year old girl with left renal pelvic calculus detected antenatally at 20 weeks was evaluated. Left hydronephrosis, obstructive pelvic calculus with decrease in differential renal function on Ethylene dicysteine (EC) renogram was confirmed. Metabolic work up was normal. Following stone extraction by left pyelolithotomy, a left ureteropelvic junction obstruction secondary to a mucosal valve was apparent which was excised and left pyeloplasty done. Stone analysis revealed 100% cystine. Differential renal function and drainage improved post -surgery. Child was lost to follow up in the interim and presented one and a half years later with a recurrent stone. Conclusion –Knowledge of antenatal urolithiasis ensures continued follow up, evaluation for metabolic disorders and associated structural defects especially with increasing stone size and increasing hydronephrosis. This helps in timely intervention and continued surveillance Keywords: antenatal, obstructive calculus, hydronephrosis, surveillance